The impact of emotional stimuli on response inhibition in an inpatient and day-hospital patient psychosomatic cohort - Westbomke, Sina; Schag, Kathrin; Derntl, Birgit; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2023)
Objectives To correctly recognize and respond to your counterpart's emotion is essential for a successful get-together. To ensure this, emotional processes and inhibitory control are linked and interact with each other. However, this interaction can be altered in several mental disorders. In a group of psychosomatic patients, we investigated possible differences in the response inhibition between neutral and emotional stimuli and whether a psychosomatic inpatient and day-hospital patient treatment influences response inhibition profiles. Methods One hundred and one patients, diagnosed with different psychiatric diagnoses (77 women, 41.43 ± 13.13 years), completed an emotional stop-signal task (ESST) and an impulsive behavior scale upon admission in an inpatient and day-hospital patient treatment on a psychosomatic ward (T0) and at discharge (T1). Patients with depressive disorders completed the test again after 1 year (follow-up measurement T2, n = 22). Emotional stimuli were angry and neutral faces. Stop-signal reaction time (SSRT) and stop-signal delay (SSD) were calculated as the main behavioral parameters. Results We found a significantly higher SSRT for neutral than angry faces at both admission (8.538 ms, p < 0.001) and discharge (11.142 ms, p < 0.001), with a matching higher SSD for angry than neutral faces at both timepoints (T0: 8.360 ms, p < 0.001, T1: (6.950 ms, p < 0.001). The SSRT for angry faces significantly decreased after treatment (-8.485 ms, p = 0.0110). For neutral faces, the decrease failed to reach significance (−5.881 ms, p = 0.250). A significant decrease in SSRT for neutral faces in patients with depressive disorders was found 1 year after discharge compared with admission (−19.040 ms, p = 0.0380). Conclusion Our data demonstrate a decreased response inhibition for neutral compared with emotional stimuli and an improved response inhibition for angry faces after discharge in a psychosomatic inpatient and day-hospital patient cohort. Additionally, patients with depressive disorders displayed a significantly better response inhibition for neutral faces 1 year after discharge compared with the baseline measurement. With this study, we provide more evidence for altered emotional response inhibition in different mental disorders and a hint that psychosomatic inpatient and day-hospital patient treatment may help to normalize it, even if the effects remained small and it needs further research to prove causality.